Risk of hemorrhage in abnormally invasive placenta according to its management. (17th September 2017) - Pinto, Pedro Viana; Machado, Ana Paula; Montenegro, Nuno
Abstract: Severe hemorrhage is a major concern during operative procedures for abnormally invasive placenta (AIP). We reviewed published literature with the objective to provide evidence of blood loss with the most common treatment options for AIP. We selected 54 articles that fulfilled the inclusion criteria. Cesarean hysterectomy, with or without occlusion balloons in the internal iliac arteries, was the treatment associated with the greatest blood loss. Major blood loss was also associated with the placenta left in situ (reported in 3 of 10 articles), and with uterine artery embolization (reported in 3 of 15 articles). The best outcomes were seen for cesarean hysterectomy with balloon occlusion of the common iliac arteries (CIA; 9 patients, including 1 with major blood loss), balloon occlusion of the abdominal aorta (27 patients, no major blood loss) and conservative surgery (99 patients, including one with major blood loss). In conclusion, cesarean hysterectomy with balloon occlusion of the CIA or abdominal aorta, and conservative treatments seem to have the best outcomes. However, our results are based on a small number of articles. Hence, it is necessary to have available more reports on the outcomes of these treatments, to arrive at a more definitive conclusion.